Development and preliminary validation of the GebStart-tool for advising nulliparous women in early labour - Susanne Grylka-Baeschlin; Nadine Pauli; Catherine Rapp; Carola Baumgartner; Clizia Iseppi; Nele Struebing; Linda Karg; Gabriela Minati; Leonhard Schäffer; Olav Lapaire; Markus Hodel; Gabriella Stocker; et al. (PLoS ONE, 2025)
Objectives Nulliparous women in early labour are unsure when to go to hospital. The aim of this study was to develop and preliminary validate a tool for advising for or against hospital admission. Methods We developed the preliminary long version of the GebStart-tool with 32 items based on focus group discussions and a scoping review. It was applied in a multicentre study with n = 394 women during their contact with the hospital. Because of the formative and complex character of the GebStart-tool, factor analysis was not appropriate. Instead, items were subdivided deductively into the domains ‘Physical symptoms’, ‘Emotional state’, Self-management’ and ‘Resources’. Distribution of response options, adjusted Cox regressions with time intervals describing care needs as outcomes and adjusted multinomial regression with the outcome ‘Care decision’ were used to reduce items and for preliminary validation. Results The reduced GebStart-tool contained 15 items and cutoff points at 22 and 33 points. The total score of the instrument was significantly associated with all time intervals describing care needs (duration between completion of the tool and hospital admission (HR = 1.08, 95% CI [1.05–1.10], p < 0.001), onset of active labour (HR = 1.06, 95% CI [1.04–1.08], p < 0.001), first use of medical pain management (HR = 1.08, 95% CI [1.06–1.11], p < 0.001), first use of alternative pain management (HR = 1.08, 95% CI [1.05–1.10], p < 0.001)). However, a higher total score of the reduced GebStart-tool was not significantly associated with a reduced risk for the decision ‘Stay at home’ (RR = 0.98, 95% CI [0.94–1.02], p = 0.421), but with a significantly higher risk for the decision ‘Hospital admission’ (RR = 1.13, 95% CI [1.05–1.22], p = 0.001) compared to ‘Keep in contact’. Conclusion We developed a practical instrument with 15 items based on scientific evidence. Further research of the GebStart-tool in larger samples is necessary. Moreover, the use in clinical practice accompanied by implementation research and translation into other languages should be envisaged.